2008
DOI: 10.1002/ibd.20243
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB and the intestine: Friend or foe?

Abstract: The biological impact of the NF-kappaB transcriptional system in various intestinal biological processes such as cellular proliferation, differentiation and survival, inflammation, and carcinogenesis is a relatively young field of research. Less than a decade ago, reviews addressing NF-kappaB regulation and function in the intestine had to borrow concepts and hypotheses from other bodily systems such as the joints (rheumatoid arthritis), the lungs (asthma), or the cardiovascular system (systemic inflammatory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 135 publications
4
65
0
3
Order By: Relevance
“…45 The protective function of NFκB in these models appears to be mediated by an anti-apoptotic response that protects the epithelium and promotes a wound healing response, two key biological processes in the case of intestinal injury. 39,46 Therefore, the concept put forward by Pagnini et al that VSL#3 prevents the development of ileitis by activating IECderived NFκB signaling appears to be in line with these reports. However, it is important to emphasize that these protective responses were mainly observed in response to overt epithelium damage induced by radiation, ischemia or chemical exposure.…”
Section: Acknowledgementssupporting
confidence: 62%
See 1 more Smart Citation
“…45 The protective function of NFκB in these models appears to be mediated by an anti-apoptotic response that protects the epithelium and promotes a wound healing response, two key biological processes in the case of intestinal injury. 39,46 Therefore, the concept put forward by Pagnini et al that VSL#3 prevents the development of ileitis by activating IECderived NFκB signaling appears to be in line with these reports. However, it is important to emphasize that these protective responses were mainly observed in response to overt epithelium damage induced by radiation, ischemia or chemical exposure.…”
Section: Acknowledgementssupporting
confidence: 62%
“…Additionally, NFκB is activated by a wide array of agents found in the intestinal milieu including bacteria, bacterial products, viruses, cytokines and growth factors. 38,39 Finally, IBD involves the dysregulated production of proinflammatory cytokines, many of which lie downstream in the activated NFκB pathway. For example, the blockade of pro-inflammatory cytokines such as TNFα and IL-12p40 with neutralizing antibodies are efficient modalities for the treatment of IBD.…”
mentioning
confidence: 99%
“…33 Moreover, TNFAIP8 protein is known to be induced by NF-κB activation, 34 a central pro-proliferative, antiapoptotic transcription factor. 35 Mechanistic studies have shown that decreased TNFAIP8 expression led to concomitant decreases in the levels of vascular endothelial growth factor receptor-2 (VEGFR-2) and matrix metalloprotease (MMP) 1 and 9. 32 In addition, TNFAIP8 has been shown to be directly coupled to Gαi g-proteins; this interaction does not appear to be involved in Gαi3-mediated cAMP inhibition but is involved in Gi-mediated inhibition of cell death, presumably via the Gβγ subunit.…”
Section: Introductionmentioning
confidence: 99%
“…Although NF-kB activation is important for production of detrimental cytokines from inflammatory cells, it is also crucial in epithelial survival from the cytotoxic insult in the gut (21,36). These beneficial effects of NF-kB in gut epithelial integrity have been reported in other diverse injury models (37)(38)(39)(40)(41). In addition to the microbial insult, specific NF-kB activators such as the bile salt taurodeoxycholate promote epithelial reconstruction after physical injury (39).…”
Section: Discussionmentioning
confidence: 93%
“…by inducing the transcription of genes involved in epithelial integrity and tissue remodeling after tissue injuries (37,38). For instance, intestinal NF-kB is important for the spatial organization of the tight junction protein ZO-1, which is vital for maintaining epithelial barrier and polarity (42).…”
Section: Discussionmentioning
confidence: 99%